The Effect of Beverages and Polishing on Color Change of Different Temporary Prosthetic Materials: In Vitro Study - Ayşe Rençber Kızılkaya; Meltem Nermin Dursun (Selcuk Dental Journal)
Objective: The aim of this study was to evaluate the effect of five different beverages and polishing on the color change of two different temporary prosthetic materials manufactured with different methods. Method: 160 (10x2 mm) disc-shaped samples were fabricated using direct (Acrytemp)(n=80) and indirect (Imident) (n=80) temporary prosthetic materials. Samples prepared using molds were divided into four groups as polished (direct/indirect material) and unpolished (direct/indirect material) (n=40 each). After initial measurement of L,a,b values using a spectrophotometer, the samples in each group were immersed in five different beverages (distilled water (DW), coffee (CF), cola (CC), sour cherry juice (CJ), red wine (RW) (n=8) and stored for 7 days. Then, the spectrophotometric measurements of the samples were repeated and the color change (ΔE00) values were calculated. Data were analyzed using a three-way-ANOVA followed by post hoc Tukey HSD test (p=0.05). Results: Greater color change was observed in the direct temporary material (p